Patch Adams - Shadyac, Tom (Universal, 1999)
Meets Patch Adams, a doctor who doesn't look, act or think like any doctor you've met before. For Patch, humor is the best medicine, and he's willing to do just about anything to make his patients laugh-even if it means risking his own career.